(untitled) (Journal of Asian Development Studies, 2025)
This study conducts a comparative analysis of sensory imagery employed in John Keats’s "ode to psyche" and "ode on melancholy," alongside Siegfried Sassoon’s "attack" and "base details," using an integrated framework combining new critical and cognitive trauma theory approaches. The findings reveal that Keats constructs a cohesive sensory ecosystem through a paradoxical structure, creating a unified, beautiful world. Moreover, his use of sensory paradox in the odes resolves the tension between beauty and pain, reflecting a special kind of magic known as aesthetic alchemy that helps readers see things in a new way. In stark contrast, Sassoon employs irony in his war poems to create a broken and disturbing world and to expose psychological trauma and social critique, leaving readers with a sense of discomfort and chaos. The interplay of paradox, irony and a carefully orchestrated imagery demonstrates the essential shift in poetic function from romantic aspirations of transcendence to modernist demands for testimony. The findings indicate that Keats’s integrative imagery creates a unified, emotional connection with readers, particularly resolving the central paradox of "ode to psyche" through imaginative temple-building. On the other hand, Siegfried Sassoon uses disintegrative imagery in "attack" to paint a picture of chaos and trauma, mirroring the disintegration of the structural coherence. This study merges the traditional analysis with cognitive and trauma theories, offering a new framework for understanding how sensory language shapes poetry’s impact across literary periods.